2014
DOI: 10.1371/journal.pone.0101771
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental Stiffness Enhances Glioma Cell Proliferation by Stimulating Epidermal Growth Factor Receptor Signaling

Abstract: The aggressive and rapidly lethal brain tumor glioblastoma (GBM) is associated with profound tissue stiffening and genomic lesions in key members of the epidermal growth factor receptor (EGFR) pathway. Previous studies from our laboratory have shown that increasing microenvironmental stiffness in culture can strongly enhance glioma cell behaviors relevant to tumor progression, including proliferation, yet it has remained unclear whether stiffness and EGFR regulate proliferation through common or independent si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
99
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 60 publications
(65 reference statements)
12
99
0
Order By: Relevance
“…Interestingly, AKT signaling has previously been implicated in SRp40-mediated splicing of the PKC family (14,16), suggesting that AKT is likely to be involved in a similar way in both stiffness-mediated PKC and EDB-FN splicing. In addition, the regulation of PI3K/AKT pathway by matrix stiffness is increasingly well documented in a number of different experimental tumor models (17)(18)(19)44). Taken together, our data uncover a fundamental mechanism regulating EDB-FN expression in ECs.…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, AKT signaling has previously been implicated in SRp40-mediated splicing of the PKC family (14,16), suggesting that AKT is likely to be involved in a similar way in both stiffness-mediated PKC and EDB-FN splicing. In addition, the regulation of PI3K/AKT pathway by matrix stiffness is increasingly well documented in a number of different experimental tumor models (17)(18)(19)44). Taken together, our data uncover a fundamental mechanism regulating EDB-FN expression in ECs.…”
Section: Discussionsupporting
confidence: 53%
“…EGFR, as a nonintegrin mechanosensor, could mediate mechanical responses, and the reports that EGF-EGFR induced chondrocyte proliferation prompted investigation to examine the involvement of EGFR in the periodic mechanical stress-induced chondrocytic mitogenic effects [34,35]. The present study showed that the specific EGFR inhibitor AG1478 and shRNA targeted to EGFR blocked chondrocyte proliferation in response to periodic mechanical stress.…”
Section: Discussionsupporting
confidence: 49%
“…Much of the early focus has been on the obvious changes in stiffness, since the stroma surrounding most tumors often becomes more rigid and dense due to an enrichment of collagen type I and fibronectin (Miles and Sikes, 2014;Pickup et al, 2014). This increase in rigidity leads to an increase in tumor cell proliferation, migration and invasion (Alexander et al, 2008;Charras and Sahai, 2014;Jerrell and Parekh, 2014;Kostic et al, 2009;Parekh and Weaver, 2009;Tilghman et al, 2010;Ulrich et al, 2009;Umesh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%